2022
DOI: 10.1155/2022/9809952
|View full text |Cite|
|
Sign up to set email alerts
|

An Intelligent Teaching Strategy of Cross-Cultural Business Communication Course Based on Big Data

Abstract: The Internet's growth has opened up new avenues for educational reform, and educational informatization has shifted the traditional classroom-teaching model. Teachers' teaching techniques have changed dramatically because of the introduction of a variety of new mobile intelligent terminals to the campus and classroom. This paper examines the design content of intelligent teaching methods against the backdrop of big data, using a cross-cultural business communication course as an example to reform the classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Firstly, through the design of the Cross-Cultural Communication knowledge module, the content system of English teaching in colleges and universities can be enriched to provide Cross-Cultural Communication support for the innovation of English teaching mechanism and effectively resolve the serious cultural misunderstandings arising from language differences [18]. In this process, English teachers can use a combination of online video viewing and classroom teaching to complete the transfer of Cross-Cultural Communication knowledge and enrich the students' cross-cultural knowledge reserves [19]. This is why English teachers need to guide their students to use advanced online information technology to search for knowledge about Cross-Cultural Communication on platforms such as the China University MOOC, and to conduct independent learning.…”
Section: Reconstructing English Teaching Modules Using Modular Teachi...mentioning
confidence: 99%
“…Firstly, through the design of the Cross-Cultural Communication knowledge module, the content system of English teaching in colleges and universities can be enriched to provide Cross-Cultural Communication support for the innovation of English teaching mechanism and effectively resolve the serious cultural misunderstandings arising from language differences [18]. In this process, English teachers can use a combination of online video viewing and classroom teaching to complete the transfer of Cross-Cultural Communication knowledge and enrich the students' cross-cultural knowledge reserves [19]. This is why English teachers need to guide their students to use advanced online information technology to search for knowledge about Cross-Cultural Communication on platforms such as the China University MOOC, and to conduct independent learning.…”
Section: Reconstructing English Teaching Modules Using Modular Teachi...mentioning
confidence: 99%
“…In this mode, viewers' choices are limited and they cannot watch the show in its entirety to their liking. In traditional mass media, the individual needs of the audience are partially satisfied by their own choices of information products on the mass market [17].…”
Section: Omnimedia Stranger Interactionmentioning
confidence: 99%
“…Data" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Security and Communication Network Has Retracted The Article...mentioning
confidence: 99%